Potential of Cherry Tree on Salt Phytoextraction (Revista Brasileira Multidisciplinar, 2015)
This study aimed to evaluate the tolerance to salt stress through the characterization of the influence of salinity on plant growth, nutrient concentration and distribution in seedlings of Amburana acreana ((Ducke) A. C. Smith). The experiment was conducted in a completely randomized design with five treatments and sixteen repetitions. The seedlings were grown on the substrate Plantmax® and, when reached 15 cm in height, were transplanted to PVC pipes filled with sand. After, they were submitted to a complete nutritive solution for adaptation during 15 days, with renewal of the solution every five days. Then, they were submitted to the treatments: complete, complete + 5 mL of NaCl, complete + 15 mL of NaCl, complete + 20 mL of NaCl, complete + 35 mL of NaCl. After 90 days, height, diameter and symptoms of toxicity were verified. The seedlings were dried, weighed and milled for analysis ofmacro and micronutrients. The conclusion was that the growth of A. acreana seedlings was limited with salinity increase, which also affected negatively the concentration of, N, P, K, Ca, Mg, Fe, Mn and Zn, making it difficult to distribute P and K on the aerial part of A. acreana seedlings.
Keywords: Amburana acrean; Phytoremediation; Nutrition.